Prevalensi dan faktor risiko infeksi cacing usus pada pemukiman kumuh di Kelurahan Tanjung Gusta, Sumatera Utara - Adelina Haryani Sinambela; Yoan Carolina Panggabean; Janry Sinaga; Lambok Siahaan (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Intestinal helminth infection remains a health problem worldwide, especially in tropical and developing countries such as Indonesia.Objective: This study was conducted to determine the prevalence, risk factors and symptoms of intestinal helminth infection in slum dwellers.Methods: The study used a cross sectional design with simple random sampling from March to October 2021 in Tanjung Gusta Village, Sunggal District, Deli Serdang Regency, North Sumatra. Participants were 196 people of all ages. Diagnosis was confirmed microscopically by direct preparation method and formol ether concentration method. Statistical analysis used Chi-square test to assess the association of risk factors and symptoms with intestinal helminth infection.Results: The prevalence of intestinal helminths is 24% consisting of mono and mixed infections. The prevalence of Ascaris lumbricoides 22,9%, Trichuris trichiura 8,1%, hookwoorm 7,6% and Hymenolepis nana 1,02%. There was a significant association between age (p=0,000), latrine use (p=0,000), pig farmer (p=0,000), sanitation (p=0,000) and hygiene (p=0,000) with intestinal helminths infection in participants.Conclusion: The risk factors for intestinal helminths infection are age, latrine use, pig raising, sanitation and hygiene.